Derivation of lowland riparian wetland deposit architecture using geophysical image analysis and interface detection. Issue 7 (16th July 2014) - Chambers, J. E.; Wilkinson, P. B.; Uhlemann, S.; Sorensen, J. P. R.; Roberts, C.; Newell, A. J.; Ward, W. O. C.; Binley, A.; Williams, P. J.; Gooddy, D. C.; Old, G.; Bai, L.
Abstract For groundwater‐surface water interactions to be understood in complex wetland settings, the architecture of the underlying deposits requires investigation at a spatial resolution sufficient to characterize significant hydraulic pathways. Discrete intrusive sampling using conventional approaches provides insufficient sample density and can be difficult to deploy on soft ground. Here a noninvasive geophysical imaging approach combining three‐dimensional electrical resistivity tomography (ERT) and the novel application of gradient and isosurface‐based edge detectors is considered as a means of illuminating wetland deposit architecture. The performance of three edge detectors were compared and evaluated against ground truth data, using a lowland riparian wetland demonstration site. Isosurface‐based methods correlated well with intrusive data and were useful for defining the geometries of key geological interfaces (i.e., peat/gravels and gravels/Chalk). The use of gradient detectors approach was unsuccessful, indicating that the assumption that the steepest resistivity gradient coincides with the associated geological interface can be incorrect. These findings are relevant to the application of this approach in settings with a broadly layered geology with strata of contrasting resistivities. In addition, ERT revealed substantial structures in the gravels related to the depositional environment (i.e., braided fluvial system) and a complex distribution of low‐permeability putty Chalk at the bedrock surface—with implications for preferential flow and variable exchange between river and groundwater systems. These results demonstrate that a combined approach using ERT and edge detectors can provide valuable information to support targeted monitoring and inform hydrological modeling of wetlands.